2012
DOI: 10.1007/s11434-012-5563-7
|View full text |Cite
|
Sign up to set email alerts
|

Research advance in failure risk and local strength failure for high arch dams

Abstract: To develop national economy and use the water resources and hydropower resources sufficiently, a lot of high arch dams, with the height of more than 200 m, have been and will be built in China. Although arch dams have good mechanical behavior, there is still failure possibility due to the huge water pressure and high stress level in dam, complex topographic and geologic conditions, formidable environment and high intensity earthquake. As one of the three main aspects concerning the safety of high arch dam, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…In field-based studies, not all factors can be identified. In this article, according to relevant studies on the safety evaluation of dams, [19][20][21] earthquakes, rainfall, and their secondary disasters (such as landslide and debris flows) are recognized as the main natural factors. The engineering factors primarily include dam material (concrete or earth-rock), dam type (arch dam or gravity dam), dam size (high, medium, or low), and dam age.…”
Section: Dag For Cascade Reservoir Systemmentioning
confidence: 99%
“…In field-based studies, not all factors can be identified. In this article, according to relevant studies on the safety evaluation of dams, [19][20][21] earthquakes, rainfall, and their secondary disasters (such as landslide and debris flows) are recognized as the main natural factors. The engineering factors primarily include dam material (concrete or earth-rock), dam type (arch dam or gravity dam), dam size (high, medium, or low), and dam age.…”
Section: Dag For Cascade Reservoir Systemmentioning
confidence: 99%
“…A thorough understanding of the initialization process and the formation of cracks and their propagation in various materials is essential in many engineering fields and applications, as one of the crucial safety and economic factors for the preservation of existing and development of new construction [1][2][3]. Although macro cracks affect the behavior of the structures on a macroscopic scale, critical micro cracking processes leading to structural failure occur in the structure of the material at the microscopic scale.…”
Section: Introductionmentioning
confidence: 99%